Data from capillary electrophoresis analysis of serum from patients with suspected multiple myeloma - Rotter Sopasakis, Victoria; Mattsson Hultén, Lillemor; Nilsson, Maria (University of Gothenburg, 2023)
Numerical data from serum capillary electrophoresis from individuals with suspected multiple myeloma.

Numeriska data från kapillärelekrofores av serum från individer med misstänkt multipelt myelom.
Data från kapillär-elektrofores-analys av serum från patienter med misstänkt multipelt myelom
Keywords: Blood Protein Electrophoresis; Blodproteinelektrofores; Electrophoresis, Capillary; Kapillärelektrofores; Multiple myeloma and malignant plasma cell neoplasms; Myelom och maligna plasmacellstumörer; Medication and treatment; Medicinering och behandlingar; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Mathematical Analysis; Matematisk analys; Computational Mathematics; Beräkningsmatematik; Probability Theory and Statistics; Sannolikhetsteori och statistik; Analytical Chemistry; Analytisk kemi; Medical Laboratory Technologies; Medicinsk laboratorieteknik; Cancer and Oncology; Cancer och onkologi; Clinical Laboratory Medicine; Klinisk laboratoriemedicin; Signs and symptoms; pathological conditions; Tecken och symtom; patologiska tillstånd